Peran Kepemimpinan Kepala Sekolah dan Profesionalisme Guru Dalam Meningkatkan Mutu Pendidikan Indonesia - Jaya Saputra; Hilalludin Hilalludin; Irham Rohib Gibran (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research aims to identify and analyze the roles of school principals' leadership, teachers' professionalism, and educational quality within the formal education system in Indonesia. The background of this study is rooted in the necessity of revolutionary leadership in educational institutions to foster moral conduct and legal compliance, with school principals as pivotal figures. The research method employed is literature review, gathering data from books, encyclopedias, documents, and scholarly journals. Findings indicate that school principals play a crucial role in motivating school members and optimizing resources to achieve educational goals. Teachers, as professional educators, bear significant responsibilities in the learning process, characterized by diligence, precision, and high integrity. Educational quality is measured through input, process, and output, influenced by both internal and external factors. The implications underscore the critical synergy between school leadership and teachers' professionalism in enhancing educational standards in Indonesia.